2020
DOI: 10.1111/corg.12313
|View full text |Cite
|
Sign up to set email alerts
|

State ownership and securities fraud: A political governance perspective

Abstract: Research question/issue This study attempts to shed new light on how the state as a controlling shareholder can affect the interests of minority shareholders by investigating the role of state ownership in deterring securities fraud commission. Research findings/insights Using archival data from a large sample of Chinese publicly traded firms, we uncover that state ownership is negatively associated with the likelihood of securities fraud commission. Further, CEO political background reinforces this negative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 117 publications
(188 reference statements)
3
47
0
Order By: Relevance
“…Second, scholars have already devoted much attention to unpacking the role of CEOs in financial misconduct in the U.S. context (Schnatterly et al, 2018), but we know less about what drives misconduct in other contexts. Studying misconduct by Chinese CEOs, therefore, adds to the empirical body of work on financial misconduct (Shi, Aguilera, & Wang, 2020). Last, China constitutes the world's second largest economy, so it seems reasonable to extend research on organizational misbehavior to this country.…”
Section: Methods Samplementioning
confidence: 99%
“…Second, scholars have already devoted much attention to unpacking the role of CEOs in financial misconduct in the U.S. context (Schnatterly et al, 2018), but we know less about what drives misconduct in other contexts. Studying misconduct by Chinese CEOs, therefore, adds to the empirical body of work on financial misconduct (Shi, Aguilera, & Wang, 2020). Last, China constitutes the world's second largest economy, so it seems reasonable to extend research on organizational misbehavior to this country.…”
Section: Methods Samplementioning
confidence: 99%
“…In line with foreign and family ownership, the integration of state ownership is only relevant in Asian studies. There are indications that state ownership reduce fraud events (Shan et al 2013;Shi et al 2020). Shi et al (2020) also found that CEO political background moderates this relationship.…”
Section: State Ownershipmentioning
confidence: 99%
“…There are indications that state ownership reduce fraud events (Shan et al 2013;Shi et al 2020). Shi et al (2020) also found that CEO political background moderates this relationship.…”
Section: State Ownershipmentioning
confidence: 99%
“…They interpret their findings as consistent with outside directors providing a weak internal monitoring mechanism as they leave precisely when shareholders need their expertise the most. Shi et al (2020) shed new light on the role of the state as a controlling shareholder and how it affects the interests of minority shareholders. Using a large sample of Chinese publicly traded firms, they find that state ownership is negatively associated with the likelihood of securities fraud.…”
Section: Highlights Of Articles Published In Volume 28mentioning
confidence: 99%